Women's Inheritance Rights Reform and the Preference for Sons in India - Sonia R. Bhalotra; Rachel Brulé; Sanchari Roy (Institute of Labor Economics (IZA), 2017)
We investigate whether legislation of equal inheritance rights for women modifies the historic preference for sons in India, and find that it exacerbates it. Children born after the reform in families with a first-born daughter are 3.8–4.3 percentage points less likely to be girls, indicating that the reform encouraged female foeticide. We also find that the reform increased excess female infant mortality and son-biased fertility stopping. This suggests that the inheritance reform raised the costs of having daughters, consistent with which we document an increase in stated son preference in fertility post-reform. We conclude that this is a case where legal reform was frustrated by persistence of cultural norms. We provide some suggestive evidence of slowly changing patrilocality norms.
Keywords: O12; K11; I21; 330; inheritance rights; ultrasound; female foeticide; sex selection; son preference; gender; India